Perbandingan Kinerja Keuangan Perusahaan Farmasi Milik BUMN dan Swasta di BEI Periode 2016-2018 - Lia Candrayani; Ziana Fitri; Kharis Fadlullah Hana (Mabsya: Jurnal Manajemen Bisnis Syariah, 2020)
The purpose of this study was to determine the comparison of the financial performance of state-owned pharmaceutical companies with private-owned pharmaceutical companies and find out what factors affect differences in company performance based on analysis of profitability, market value rations and EVA. This study using a quantitative approach using a comparative descriptive method that took a sample of 4 pharmaceutical companies listed on the Stock Excahange. The data analysis technique uses a different independent sample T-test by comparing financial data from state-owned and private pharmaceutical companies in the 2016-2018 period. The results of the study show that return on equity (ROE) analysis of state-owned pharmaceutical companies is not safe because there are significant differences in the precentage above 15% and private pharmaceutical above 15%. The earning per share (EPS) analysis results of state-owned companies reached 0,35 and private pharmaceutical companies reached 50,71. As well as economic value added (EVA) analysis produces data there are differences in financial performace where the state-owned pharmaceutical companies have increased and privat pharmaceutical companies have decreased.